The Influence of Da'wah Content on Social Media on Generation Z's Religious Understanding at STAI Balikpapan - Annisa Yuniar Fakhiriyah; Iskandar Yusuf (Universitas Dharmawangsa Medan, 2025)
This study aims to determine the influence of da'wah content on social media on the religious understanding of generation Z, with the research subject of students of the Islamic Religious College (STAI) Balikpapan. The background of this research is based on the increasing use of social media as a medium for spreading da'wah among the younger generation. The method used is a quantitative method with a survey approach. The sample in this study amounted to 30 students who were selected purposively, with active criteria using social media and included in the age category of Generation Z. Data collection techniques used questionnaires, and data analysis was carried out by simple linear regression test. The results of the study showed that there was no significant influence between da'wah content on social media on students' religious understanding. These findings indicate that exposure to da'wah content on social media has not been effective enough in increasing religious understanding among the younger generation. Therefore, it is recommended that da'wah content be packaged in a more attractive, interactive, and tailored to the characteristics of Generation Z to increase the effectiveness of the religious message conveyed.